Preoperative Planning for EndoAnchor Use During Thoracic Endovascular Aortic Repair in the Distal Aortic Arch. (April 2021) - de Beaufort, Hector W. L.; Lovato, Luigi; Valdivia, Andrés Reyes; Kratimenos, Theodoros; Rossi, Giovanni; Rousseau, Hervé; Riambau, Vicente; Heijmen, Robin H.
Purpose: To describe steps related to intraoperative C-arm orientations that can be taken during preoperative planning of thoracic stent-graft repair to facilitate the deployment of EndoAnchors in the distal aortic arch. Technique: Previous experience from transcatheter aortic valve implantation (TAVI) may be helpful in addressing issues with C-arm orientation. In TAVI, preoperative computed tomography (CT) images are routinely obtained to generate a patient-specific curve that represents a virtually complete rotation of the C-arm perpendicular to the annulus. The curve clearly demonstrates that each adjustment in cranial or caudal view needs parallax correction in the left or right anterior oblique direction to remain perpendicular, and vice versa. This experience can be translated to the preoperative planning of EndoAnchor use in the aortic arch. By placing markers along the circumference of the proximal landing zone of the preoperative CT scan, the required C-arm orientations can be determined for each marker. Conclusion: Determining the optimal C-arm orientation during preoperative planning will facilitate successful EndoAnchor deployment and may contribute to improved durability of endovascular repair in hostile necks in the aortic arch.